Universal Prenatal Chromosomal Microarray Analysis: Additive Value and Clinical Dilemmas in Fetuses with a Normal Karyotype - Bornstein, Eran; Berger, Sharon; Cheung, Sau W.; Maliszewski, Kristen T.; Patel, Ankita; Pursley, Amber N.; Lenchner, Erez; Bacino, Carlos; Beaudet, Arthur L.; Divon, Michael Y. (American Journal of Perinatology, 2017)
Objective To assess the additive value of prenatal chromosomal microarray analysis (CMA) for all indications and the likelihood of detecting pathologic copy number variations (CNVs) based on specific indications.Methods A retrospective analysis was performed on amniocentesis and chorionic villi sampling results obtained between 2010 and 2014 in a single institution. A total of 3,314 consecutive patients undergoing invasive genetic testing for different indications were offered CMA in addition to standard karyotype. The prevalence of pathologic CNVs was compared between patients with low-risk indications and those with high-risk indications. Likewise, the prevalence of pathologic CNVs among patients with different sonographic abnormalities was calculated and compared with the low-risk group. Chi-square and Fisher exact tests were used for statistical analysis.Results The prevalence of pathologic CNVs was significantly higher in patients with high-risk indications and specifically those with sonographic abnormalities, compared with the low-risk group (2.8 and 5.9% vs. 0.4%, respectively; all p < 0.05).Conclusion Prenatal CMA detected clinically relevant CNVs in fetuses with a normal karyotype. Major structural malformations and nuchal translucency (NT) ≥ 3.0 mm are associated with the highest risk for a CMA abnormality. Nevertheless, the prevalence of pathologic CNVs in the low-risk population was high enough (1:250) to consider genetic counseling in this group.
Keywords: chromosomal microarray; genetic counseling; karyotype; prenatal diagnostic test